The Effects of Social Psychological Variables and Gender on the Grade Point Averages and Educational Expectations of University Students: A Case Study - Clifton, Rodney A. (Canadian Journal of Higher Education, 2017)
This paper uses a social psychological model to examine the educational attainment and expectations of 569 male and female Education students enrolled in a major university in Western Canada. Structural equation modeling was used to examine the effects of gender on six social psychological variables (positive affect, negative affect, interaction with students, interaction with professors, motivation, and self-concept of ability) and the effects of gender and the social psychological variables on the students' grade point averages and educational expectations. In comparison with males, females had higher positive affect and more positive motivation. Two of the social psychological variables, self-concept of ability and interaction with students, had strong effects on grade point average and slightly weaker effects on educational expectations. When the interaction effects of gender and the social psychological variables were added to the analyses, slight increases in the explained variance in grade point average and educational expectations were evident. Females had slightly higher grade point averages than males and males had slightly higher educational expectations than females.